PERANAN FRONT DESK AGENT DALAM PENANGANAN KELUHAN TAMU PADA HOTEL SWISS-BELINN LEGIAN - Yosefin Ni Wayan Haryandini; Ni Luh Putu Sri Widhiastuty (Journal of Tourism and Interdiciplinary Studies, 2022)
The purpose of this study was to determine the role of the front desk agent in handling guest complaints and the constraints faced by the front desk agent in handling guest complaints so that it can be seen the efforts made by the front desk agent in overcoming guest complaints. This research uses data collection techniques in the form of interviews, observation, and documentation with qualitative descriptive data analysis techniques. The research focus on pieces of information from the informant which later data check by triangulation to others. The research found out that (a) What should be known is the duties and responsibilities of the front desk agent so that it can be implemented on the role of the front desk agent in handling guest complaints, (b) by presenting the results of interviews, observations and documentation it can be concluded that the front desk agent plays a very important role in handling guest complaints, (c) the effort done by the front desk agent to handle the complaints includes following SOP, coordination, join the briefing regularly, increase the communication skill and keep the hospitality attitude to make everyone feel comfort during their stay.